A new case of Mycoplasma hominis mediastinitis and sternal osteitis after cardiac surgery. (February 2015) - Le Guern, Rémi; Loïez, Caroline; Loobuyck, Valentin; Rousse, Natacha; Courcol, René; Wallet, Frédéric
Highlights: Mycoplasma hominis has become an established cause of mediastinitis. M. hominis is not usually covered by the empiric antimicrobial therapy. A prolonged incubation may help to recover M. hominis but not Ureplasma spp. 16S rDNA sequencing is useful in case of culture negative mediastinitis. Abstract: We report a case of nosocomial mediastinitis and sternal osteitis due to M. hominis after open-heart surgery in an immuno-competent patient. This infection has been diagnosed by incubating the culture media for an extended period of time, and sequencing 16S rDNA directly from the clinical samples.